2014
DOI: 10.1123/ijsnem.2013-0106
|View full text |Cite
|
Sign up to set email alerts
|

Oral L-Arginine Before Resistance Exercise Blunts Growth Hormone in Strength Trained Males

Abstract: Acute resistance exercise and L-arginine have both been shown to independently elevate plasma growth hormone (GH) concentrations; however, their combined effect is controversial. The purpose was to investigate the combined effects of resistance exercise and L-arginine supplementation on plasma L-arginine, GH, GH secretagogues, and IGF-1 in strength trained participants. Fourteen strength trained males (age: 25 ± 4 y; body mass: 81.4 ± 9.0 kg; height: 179.4 ± 6.9 cm; and training experience: 6.3 ± 3.4 y) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
(63 reference statements)
0
7
1
Order By: Relevance
“…These authors reported that arginine administration failed to impact muscle protein synthesis or femoral artery blood flow. Growth hormone levels did rise in response to arginine ingestion, which contrasts with the findings of Forbes et al, [ 275 ] who reported a blunting of growth hormone production after acute ingestion of arginine in strength trained males. Regardless, the Tang study [ 274 ] and others [ 276 , 277 ] failed to link the increase in growth hormone to changes in rates of muscle protein synthesis.…”
Section: Introductioncontrasting
confidence: 99%
“…These authors reported that arginine administration failed to impact muscle protein synthesis or femoral artery blood flow. Growth hormone levels did rise in response to arginine ingestion, which contrasts with the findings of Forbes et al, [ 275 ] who reported a blunting of growth hormone production after acute ingestion of arginine in strength trained males. Regardless, the Tang study [ 274 ] and others [ 276 , 277 ] failed to link the increase in growth hormone to changes in rates of muscle protein synthesis.…”
Section: Introductioncontrasting
confidence: 99%
“…The other possibility resides in the ability of citrulline to shift the energy metabolism to more anaerobic pathways and ameliorating mitochondria activity, through antioxidant properties [35]. Otherwise, L-Arginine has also been shown to stimulate the release of growth hormone (GH) [36,37], which is a potent anabolic agent that favors cell growth and body energetics, which promotes muscle hypertrophy [38,39]. Many effects of L-Arginine supplementation are also linked to improved carbohydrate oxidation and oxygen efficiency [40,41], with reduced exercise-induced production of ammonia, lactate, fatty acids, and fat oxidation [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Analogical data indicates S Forbes.et al (2014) [31], they state that usage bigger amounts of L-arginine increases the concentration of growth hormone in strength trained males. However, ARGI+ in combination with Multi Maca supplementation more influences aerobic capacity (p = 0,047 and p = 0,048).…”
Section: Discussionmentioning
confidence: 94%